Features of the Crystal and Electronic Structures of the Zr1-xYxNiSn Semiconductor - Krayovskyy, Roman; Romaka, Vitaly; Bovgyra, Oleg (Видавництво Національного університету «Львівська політехніка», 2009)
Crystal and electronic structures of the heavy, Y impurity, dopez ZrNiSn intermetallic semiconductor (Na=3,8*10/4,8*10cm)were investigated. It is rotined that alloing of n- ZrNiSn is accompaid arrangement of crystalline structure, the atoms of admixture occupy positions of atoms of Zr only, generating the defects of occeptor-type nature. Set area of existence of solid solution of Zr1-xYxNiSn, dependence, between the concentration of solid solution and direction and speed of drift of lever to Fermi, by the transition of conductivity dielectric-metal.
Keywords: temperature; thermometry; thermometric element; semiconductor